Discharge Hospice Referral and Lower 30-Day All-Cause Readmission in Medicare Beneficiaries Hospitalized for Heart Failure. (July 2015) - Kheirbek, Raya E.; Fletcher, Ross D.; Bakitas, Marie A.; Fonarow, Gregg C.; Parvataneni, Sridivya; Bearden, Donna; Bailey, Frank A.; Morgan, Charity J.; Singh, Steven; Blackman, Marc R.; Zile, Michael R.; Patel, Kanan; et al.
<x xml:space="preserve">Abstract</x> Background— Heart failure (HF) is the leading cause for hospital readmission. Hospice care may help palliate HF symptoms but its association with 30-day all-cause readmission remains unknown. Methods and Results— Of the 8032 Medicare beneficiaries hospitalized for HF in 106 Alabama hospitals (1998–2001), 182 (2%) received discharge hospice referrals. Of the 7850 patients not receiving hospice referrals, 1608 (20%) died within 6 months post discharge (the hospice-eligible group). Propensity scores for hospice referral were estimated for each of the 1790 (182+1608) patients and were used to match 179 hospice-referral patients with 179 hospice-eligible patients who were balanced on 28 baseline characteristics (mean age, 79 years; 58% women; 18% non-white). Overall, 22% (1742/8032) died in 6 months, of whom 8% (134/1742) received hospice referrals. Among the 358 matched patients, 30-day all-cause readmission occurred in 5% and 41% of hospice-referral and hospice-eligible patients, respectively (hazard ratio associated with hospice referral, 0.12; 95% confidence interval, 0.06–0.24). Hazard ratios (95% confidence intervals) for 30-day all-cause readmission associated with hospice referral among the 126 patients who died and 232 patients who survived 30-day post discharge were 0.03 (0.04–0.21) and 0.17 (0.08–0.36), respectively. Although 30-day mortality was higher in the hospice referral group (43% versus 27%), it was similar at 90 days (64% versus 67% among hospice-eligible patients). Conclusions— A discharge hospice referral was associated with lower 30-day all-cause readmission among hospitalized patients with HF. However, most patients with HF who died within 6 months of hospital discharge did not receive a discharge hospice referral.